2019
DOI: 10.1051/0004-6361/201834941
|View full text |Cite
|
Sign up to set email alerts
|

Single metal-poor ultra compact dwarf galaxy at one kiloparsec distance from the low-mass elliptical galaxy FCC 47

Abstract: Context. Photometric surveys of galaxy clusters have revealed a large number of ultra compact dwarfs (UCDs) around predominantly massive elliptical galaxies. Their origin is still debated as some UCDs are considered to be the remnant nuclei of stripped dwarf galaxies while others seem to mark the high-mass end of the star cluster population. Aims. We aim to characterise the properties of a UCD found at very close projected distance (r proj = 1.1 kpc) from the centre of the low-mass (M ∼ 10 10 M ) early-type ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 142 publications
3
19
0
Order By: Relevance
“…The simultaneous extraction of the metallicity of both the NSC and the galaxy stellar body showed that these NSCs are more metal-poor than their hosts, suggesting that they have formed through the process of in-spiraling GCs. Intriguingly, the masses, sizes, and metallicities of these two NSCs are consistent with the properties of known ultra-compact dwarfs (Misgeld & Hilker 2011;Voggel et al 2018Voggel et al , 2020Fahrion et al 2019a), suggesting that stripped nuclei of dwarf galaxies are the progenitors of low-mass ultra-compact dwarfs (Strader et al 2013).…”
Section: )?supporting
confidence: 79%
“…The simultaneous extraction of the metallicity of both the NSC and the galaxy stellar body showed that these NSCs are more metal-poor than their hosts, suggesting that they have formed through the process of in-spiraling GCs. Intriguingly, the masses, sizes, and metallicities of these two NSCs are consistent with the properties of known ultra-compact dwarfs (Misgeld & Hilker 2011;Voggel et al 2018Voggel et al , 2020Fahrion et al 2019a), suggesting that stripped nuclei of dwarf galaxies are the progenitors of low-mass ultra-compact dwarfs (Strader et al 2013).…”
Section: )?supporting
confidence: 79%
“…Being a ETG in the outskirts of the Fornax cluster, the wealth of complexity in this galaxy has been surprising: we found two KDCs, a sharp central metallicity peak and FCC 47-UCD1. As we argue in Fahrion et al (2019), the UCD could be the stripped nucleus of a disrupted dwarf galaxy and would therefore indicate a minor merger in FCC 47's past. In addition, the KDCs most likely are evidence of at least one major merger event that has altered the kinematic structure of the galaxy significantly.…”
Section: Discussionmentioning
confidence: 73%
“…Further evidence that our 3 UCDs are the remnants of stripped galaxies comes from their physical sizes, which are all over 30 pc. Size was also used recently by Fahrion et al (2019) to support the stripped nucleus origin for a UCD they observed in the Fornax cluster. Using MUSE on the VLT, they measured an old age (> 8 Gyr) and low metallicity ([Z/H] = -1.12).…”
Section: Discussionmentioning
confidence: 99%